VEGF- and VEGFR2-Targeted Liposomes for Cisplatin Delivery to Glioma Cells - Shein, Sergey A; Kuznetsov, Ilya I; Abakumova, Tatiana O; Chelushkin, Pavel S; Melnikov, Pavel A; Korchagina, Anna A; Bychkov, Dmitry A; Seregina, Irina F; Bolshov, Mikhail A; Kabanov, Alexander V; Chekhonin, Vladimir P; Nukolova, Natalia V (Molecular pharmaceutics, 2016)
Targeted delivery of anticancer drugs to brain tumors, especially glioblastoma multiforme, which is the most frequent and aggressive type, is one of the important objectives in nanomedicine. Vascular endothelial growth factor (VEGF) and its receptor type II (VEGFR2) are promising targets because they are overexpressed by not only core tumor cells but also by migrated glioma cells, which are responsible for resistance and rapid progression of brain tumors. The purpose of the present study was to develop the liposomal drug delivery system combining enhanced loading capacity of cisplatin and high binding affinity to glioma cells. This was achieved by using of highly soluble cisplatin analogue, cis-diamminedinitratoplatinum(II), and antibodies against the native form of VEGF or VEGFR2 conjugated to liposome surface. The developed drug delivery system revealed sustained drug release profile, high affinity to antigens, and increased uptake by glioma C6 and U-87 MG cells. Pharmacokinetic study on glioma C6-bearing rats revealed prolonged blood circulation time of the liposomal formulation. The above features enabled the present drug delivery system to overcome both poor pharmacokinetics typical for platinum formulations and low loading capacity typical for conventional liposomal cisplatin formulations.